Mechanistic understanding of the size effect on shock facilitated dislocation nucleation at semicoherent interfaces. (15th March 2020) - Liu, Z.R.; Yao, B.N.; Legut, D.; Kong, X.F.; Germann, T.C.; Zhang, H.J.; Zhang, R.F.
Abstract: Interface-facilitated dislocation nucleation dominates deformation behaviors of metallic nanolaminates under shock loadings. Recent works demonstrated a strong size effect of dislocation nucleation for bimetal nanolaminates. Herein, we demonstrate that such effect is attributed to stress effect of misfit dislocations originating from neighboring interfaces, which is consistent with analytical solutions to the coupled stress fields of misfit dislocations. When changing the relative position of neighboring layers, the size effect is modified because of the variational stress. These findings provide a rational evaluation on the observed size effect of dislocation nucleation, and a foundation in designing strong shock-resistant materials by interface engineering. Graphical abstract: Image, graphical abstract